A Novel Lactose/MCC/L-HPC Triple-Based Co-Processed Excipients with Improved Tableting Performance Designed for Metoclopramide Orally Disintegrating Tablets - Xiaorong Dai; Jiamin Wang; Bo Yan; Qian Wang; Yan Shen; Yongkang Chen; Yu Tian (MDPI AG, 2024)
New co-processed excipients comprising lactose (filler and sweetener), microcrystalline cellulose (MCC, filler), and low-substituted hydroxypropyl cellulose (L-HPC, disintegrant and binder) were developed via solvent evaporation for the preparation of metoclopramide orally disintegrating tablets (MCP ODTs). Single-factor and Box-Behnken experimental designs were employed to optimize the formulation. The optimized formulation ratios were water: MCC: lactose (g/g) = 17.26:2.79:4.54:1. The results demonstrated that particles formed by solvent evaporation had superior flowability and compressibility compared to the physical mixture. Tablets compressed with these co-processed excipients exhibited a significantly reduced disintegration time of less than 25 s and achieved complete dissolution within 5 min. Pharmacokinetic studies revealed that MCP ODTs significantly improved Cmax, which was 1.60-fold higher compared to conventional tablets. In summary, the lactose/L-HPC/MCC triple-based co-processed excipients developed in this study are promising and could be successfully utilized in orally disintegrating and fast-release tablets.